Selective Extraction of Organic Contaminants from Soil Using Pressurised Liquid Extraction - Rozita Osman; Norashikin Saim (Journal of Chemistry)
This study focuses on the application of sorbents in pressurised liquid extraction (PLE) cell to establish a selective extraction of a variety of organic contaminants (polycyclic aromatic hydrocarbons (PAHs), chlorpyrifos, phenol, pentachlorophenol, and sterols) from soil. The selectivity and efficiency of each sorbent depend on the properties of the material, extracting solvent, capacity factor, organic compounds of interest, and PLE operating parameters (temperature, pressure, and extraction time). Several sorbents (silica, alumina, and Florisil) were evaluated and with the proper choice of solvents, polar and nonpolar compounds were successfully separated in two fractions. Nonpolar compounds (PAHs, chlorpyrifos, and pentachlorophenol) were recovered in the first fraction using a polar sorbent such as Florisil or alumina, and n-hexane as eluting solvent, while more polar compounds (phenol and sterols) were recovered in the second fraction using methanol. Silica (5 g) was found to be effective for selective extraction with the satisfactory recoveries for all compounds (PAHs from 87.1–96.2%, chlorpyrifos 102.9%, sterols from 93.7–100.5%, phenol 91.9%, and pentachlorophenol 106.2%). The efficiency and precision of this extraction approach and the existing EPA Method 3545 were compared.